Pelatihan Instalasi dan Troubleshooting Sistem Audio untuk Pengurus Mushola Aljabbar Desa Tawangrejo Winong Kabupaten Pati - Ahmad, Fahrudin; Supari; Margiantono, Agus; Pinandita, Satria (Faculty of Engineering, Universitas Semarang, 2026)
This community service program was conducted to enhance the technical abilities of the management team of Mushola Aljabbar, Tawangrejo, Pati regency, in operating and maintaining the audio system used for religious and social activities. The main problems identified include limited knowledge of audio installation, insufficient understanding of maintenance procedures, and difficulties in handling minor technical issues. The program employed a participatory training method that consisted of theoretical sessions, hands-on installation practice, maintenance activities, and troubleshooting simulations. Participants also took pre-test and post-test evaluations. The results indicate a significant improvement in participants’ competencies, demonstrated by an average score increase of 39.16%. Participants were able to perform basic installation, conduct routine maintenance, and independently solve common technical problems. This program had a positive impact on improving audio quality in the mushola and increasing the management’s self-reliance. Continuous training is recommended to ensure adaptability to technological developments in audio systems.